Manajemen Pendidikan Karakter Kedisiplinan di Sekolah Boarding School: Sebuah Pendekatan Kualitatif - Ina Choriyati; Sri Astuti Iriyani (CV. Global Cendekia Inti, 2025)
This study aims to describe the management of character education in boarding schools. The focus of the study includes the planning, implementation, and evaluation of character building in the context of boarding school life, which is characterized by the integration of formal education, religious habits, and intensive supervision. This study uses a qualitative approach with a field study type. Data were obtained through observation, in-depth interviews, and documentation at a boarding school in East Java. The results show that character education management for discipline is carried out through the planning of shared values and rules, the implementation of consistent habits with the example set by boarding school teachers, and daily and monthly evaluations based on reflection on student behavior. These findings reinforce the relevance of Imam al-Ghazali's concept of character education management regarding the importance of riyadhah al-nafs (spiritual training) and Ibn Khaldun's idea of the role of the environment (al-'umran) in shaping behavior. This study confirms that effective management in boarding schools must place discipline not only as a rule but as a process of continuous character building.